2004
DOI: 10.2337/diabetes.53.2.426
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretion in Type 1 Diabetes

Abstract: Type 1 diabetes, a chronic autoimmune disease, causes destruction of insulin-producing ␤-cells over a period of years. Although many markers of the autoimmune process have been described, none can convincingly predict the rate of disease progression. Moreover, there is relatively little information about changes in insulin secretion in individuals with type 1 diabetes over time. Previous studies document C-peptide at a limited number of time points, often after a nonphysiologic stimulus, and under non-steady-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
132
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 51 publications
7
132
0
3
Order By: Relevance
“…We found that patients with autoantibody negative diabetes have a highly preserved beta cell function after 20 years in contrast to antibody positive patients. This is well in line with what has previously been described for T1D [1,2] but in contrast to the general view of progressive beta cell damage in T2D [3].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that patients with autoantibody negative diabetes have a highly preserved beta cell function after 20 years in contrast to antibody positive patients. This is well in line with what has previously been described for T1D [1,2] but in contrast to the general view of progressive beta cell damage in T2D [3].…”
Section: Discussionsupporting
confidence: 92%
“…Type 1 and type 2 diabetes are different in terms of aetiology and clinical course but have both been proposed to be associated with progressive beta cell damage [1][2][3]. However, this notion has been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…This disease has an insipid beginning and may take years before it can be recognized as clinical hyperglycemia. While it is traditionally thought that the majority of BCM is destroyed at the time of presentation with diabetes, several recent studies have suggested that there may be significant residual insulin-secretory capacity on diagnosis [3]. Moreover, there is a long preclinical period during which an immunologic assault is believed to occur on the islets of Langerhans and that hyperglycemia only develops when a critical mass of β cells is lost and insulin requirement increases.…”
Section: Introductionmentioning
confidence: 99%
“…Alloxan, however, is a well-known diabetogenic agent itself; thus, the clinical utility of this approach remains unproven [15]. Dithizone and sulfonylurea receptor ligands (e.g., 3 H glibenclamide) have been studied as possible imaging agents [16], but some show broad tissue distributions of uptake contraindicating feasibility [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In type 1 diabetes, autoimmune destruction of pancreatic beta cells leads to absolute deficiency of insulin secretion with subsequent hyperglycaemia [1]. It is commonly assumed that type 1 diabetes becomes clinically apparent when the remaining beta cell mass (BCM) has decreased to 5-20% [2,3]. Recent studies, however, suggest that patients with type 1 diabetes may still have a large amount of remaining beta cells [4]; in some patients loss of BCM was less than 50% [5].…”
Section: Introductionmentioning
confidence: 99%